Option E. None of the above.

Step-by-step explanation:

From the question given above, the following data were obtained:

f(x) = (x – 5)/(2x + 3)

Inverse of f(x) => f¯¹(x) =?

Recall:

When a function f(x) is multiplied by it's inverse f¯¹(x), the result is equal to 1 i.e

f(x) × f¯¹(x) = 1

With the above information, we can determine the inverse of function given above as follow:

f(x) = (x – 5)/(2x + 3)

Inverse of f(x) => f¯¹(x) =?

f(x) × f¯¹(x) = 1

(x – 5)/(2x + 3) × f¯¹(x) = 1

f¯¹(x)(x – 5) / (2x + 3) = 1

Cross multiply

f¯¹(x)(x – 5) = (2x + 3)

Divide both side by (x – 5)

f¯¹(x) = (2x + 3) / (x – 5)

Thus, the inverse of the function is (2x + 3) / (x – 5).

Option E gives the correct answer to the question.

## Related Questions

1. Nonpoint source loads are chemical masses that travel to the main stem of a river in flows that are distributed over relatively long stream reaches. Suppose source loads are known to have a mean value of 73 and a standard deviation of 10. We will take a random sample of 48 loads and calculate the sample mean, X. (a) What is the mean of X

The sample mean of X is 73.

Step-by-step explanation:

We are given the following information in the question:

Mean, μ = 73

Standard Deviation, σ = 10

Sample size, n = 48

We have to calculate the sample mean of X

Sample mean:

• The best approximator of the sample mean is the population mean itself.

Thus, we can write:

Thus, the sample mean of X is 73.

F(x)=3x-7 and g(x)=(1/3)x+7 are inverses of each other.

.True
.False

False

Step-by-step explanation:

Sorry for the lat reply hopefully you still have that question ready. But basically in order for these equations to be considered inverses of one another it has to map its domain value and switch it to the range value and in this case it does not match the inverse when graphed.

The functions f(x) = 3x - 7 and g(x) = (1/3)x + 7 are inverses of each other.

### Explanation:

Two functions are inverses of each other if the composition of the functions results in the identity function. To check if f(x) = 3x - 7 and g(x) = (1/3)x + 7 are inverses, we need to find their composition.

Let's substitute g(x) into f(x) and simplify: f(g(x)) = f((1/3)x + 7) = 3((1/3)x + 7) - 7 = x + 7 - 7 = x.

Since f(g(x)) = x, it means that f(x) and g(x) are inverses of each other, and therefore the statement is True.

brainly.com/question/38141084

#SPJ2

tammy is 5 years younger than doris . in 4 years doris will be twice as old as tammy. how old is tammy now ​

Tammy is currently 1, and Doris is 6 in 4 years, Tammy will be 5 and Doris will be 10

Step-by-step explanation:

T=D-5

1+4=5

6+4=10

David just accepted a job at a new company where he will make an annual salary of $69000. David was told that for each year he stays with the company, he will be given a salary raise of$2500. How much would David make as a salary after 4 years working for the company? What would be his salary after t t years?

After 4 years working for the company, he would make $79,000 of salary. His salary after t years will be: [te]S(t) = 69000 + 2500t[/tex] Step-by-step explanation: David just accepted a job at a new company where he will make an annual salary of$69000. David was told that for each year he stays with the company, he will be given a salary raise of $2500. This means that after t years, his salary will be given by: [te]S(t) = 69000 + 2500t[/tex] How much would David make as a salary after 4 years working for the company? [te]S(4) = 69000 + 2500*4 = 69000 + 10000 = 79000[/tex] After 4 years working for the company, he would make$79,000 of salary.

Ifā=r, then which of the following are true statements?Check all that apply.
O A. n1/r = a
✓ B. = a
c. a1/nur
O D. a' = n.

B. a = rⁿ

C. a¹/ⁿ = r

Step-by-step explanation:

ⁿ√a = r

The above expression can be simplified as follow:

1. ⁿ√a = r

Recall:

ⁿ√a = a¹/ⁿ

Therefore,

a¹/ⁿ = r

2. ⁿ√a = r

Take the n square of both side

(ⁿ√a)ⁿ = rⁿ

(a¹/ⁿ)ⁿ = rⁿ

a = rⁿ

Help plsssssssssssss